The relationship between latent tuberculosis infection and acute myocardial infarction. - Miranda, Gustavo (2018)
Background: Tuberculosis has been associated with an increased risk of cardiovascular disease (CVD), including acute myocardial infarction (AMI). We investigated whether latent tuberculosis infection (LTBI) is associated with AMI. Methods: We conducted a case-control study in 2 large national public hospital networks in Lima, Peru, between July 2015 and March 2017. Case patients were patients with a first time diagnosis of type 1 (spontaneous) AMI. Controls were patients without a history of AMI. We excluded patients with known human immunodeficiency virus infection, tuberculosis disease, or prior LTBI treatment. We used the QuantiFERON-TB Gold In-Tube assay to identify LTBI. We used logistic regression modeling to estimate the odds ratio (OR) of LTBI in AMI case patients versus non-AMI controls. Results: We enrolled 105 AMI case patients and 110 non-AMI controls during the study period. Overall, the median age was 62 years (interquartile range, 56–70 years); 69% of patients were male; 64% had hypertension, 40% dyslipidemia, and 39% diabetes mellitus; 30% used tobacco; and 24% were obese. AMI case patients were more likely than controls to be male (80% vs 59%; P < .01) and tobacco users (41% vs 20%; P < .01). LTBI was more frequent in AMI case patients than in controls (64% vs 49% [P = .03]; OR, 1.86; 95% confidence interval [CI], 1.08–3.22). After adjustment for age, sex, hypertension, dyslipidemia, diabetes mellitus, tobacco use, obesity, and family history of coronary artery disease, LTBI remained independently associated with AMI (adjusted OR, 1.90; 95% CI, 1.05–3.45). Conclusions: LTBI was independently associated with AMI. Our results suggest a potentially important role of LTBI in CVD.